2005
DOI: 10.1097/01.fjc.0000175879.14994.63
|View full text |Cite
|
Sign up to set email alerts
|

Altered Vascular Reactivity in Mice Made Hypertensive by Nitric Oxide Synthase Inhibition

Abstract: This study tested the hypothesis that nitric oxide (NO) synthase inhibition in mice would result in hypertension characterized by increased agonist-induced vasoconstrictor responsiveness and attenuated endothelium-dependent vasodilation. Administration of N-nitro-L-arginine (L-NNA), an NO synthase inhibitor (1 g/L, 4 weeks), via drinking water to mice resulted in significant elevations in blood pressure. Phenylephrine-induced contraction was significantly increased in aortic rings from L-NNA-treated mice compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
21
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
10
21
1
Order By: Relevance
“…The peak increases in MAP were observed 3 days after the NOS inhibition protocol was started (105 Ϯ 3.8 for TRPV4 KO vs. 99.3 Ϯ 3.8 mmHg for WT, n ϭ 8 for each group) and returned toward baseline levels by day 5. Although the effect of L-NNA on MAP was transient in both groups, as has been observed in other studies employing mice (20), the present findings clearly indicate that TRPV4 channels can have a moderating effect on MAP during NOS inhibition-induced hypertension.…”
Section: Trpv4 Gene Deletion Exacerbates Nos Inhibition-induced Hypersupporting
confidence: 85%
“…The peak increases in MAP were observed 3 days after the NOS inhibition protocol was started (105 Ϯ 3.8 for TRPV4 KO vs. 99.3 Ϯ 3.8 mmHg for WT, n ϭ 8 for each group) and returned toward baseline levels by day 5. Although the effect of L-NNA on MAP was transient in both groups, as has been observed in other studies employing mice (20), the present findings clearly indicate that TRPV4 channels can have a moderating effect on MAP during NOS inhibition-induced hypertension.…”
Section: Trpv4 Gene Deletion Exacerbates Nos Inhibition-induced Hypersupporting
confidence: 85%
“…Surprisingly, acetylcholine-induced vasorelaxation of vessels from mice treated chronically with L-NAME was attenuated following acute treatment with L-NAME, the soluble guanylate cyclase inhibitor ODQ, and indomethacin, but not indomethacin alone. This suggests that chronic L-NAME treatment may not completely abolish NO synthesis, as has been previously observed with chronic administration of N -nitro-L-arginine (19). If NOS inhibition was incomplete under the conditions of our experiment, the residual source of NO appears to be lost upon induction of diabetes, since we found that acetylcholineinduced vasorelaxation was unaffected by L-NAME ϩ ODQ in mesenteric arteries from diabetic mice chronically treated with L-NAME.…”
Section: Discussionsupporting
confidence: 71%
“…24 The aorta was used in this protocol because many previous studies have suggested that levels of basal NO are higher in the aorta than in smaller vessels. In brief, aortic rings were connected to a force transducer at a final tension of 0.5 g. Dose-response curves to phenylephrine were obtained.…”
Section: Vasomotor Studies In Vitromentioning
confidence: 99%